Trends in State Education Policy in Greece: 1976 to the 1997 Reform - Nikos M. Georgiadis (Arizona State University, 2005)
This article deals with the education policy in Greece during the period 1976 to 1997, with special focus on the policy that is in practice since 1997. During the early 1990s, the important changes at international and local levels had established the foundations for this policy, which is significantly different from the ones implemented during the twenty five years before that and has effected a total transformation of the Greek educational system. The analysis of this policy, including a comparison with those that preceded it (through the study of the relevant reforms and major regulations), as well as with the "restructuring" education policies implemented in several other countries during the last 15 years, is followed by an assessment of its results to the present.